Clinical and laboratory presentation of von Willebrand disease: Experience from a single center in Saudi Arabia - Tarek Owaidah, MD; Muhammed Alharbi, MD; Mohammed Mandourah, MD; Mahasen Saleh, MD; Abdulrahman Almusa, MD; Randa Alnounou, MD; Hazza Alzahrani, MD; Haithm Khogeer, MD (Journal of Taibah University Medical Sciences, 2023)
الملخص: أهداف البحث: لتقييم العرض السريري والنتائج المعملية بين المرضى الذين تم تشخيص إصابتهم بمرض فون ويلبراند في وحدة الرعاية الثالثة في السعودية. طريقة البحث: تضمنت هذه الدراسة بأثر رجعي 189 مريضًا يعانون من مرض فون ويلبراند تمت متابعتهم في وحدتنا على مدار أربع سنوات ، وتم جمع البيانات السريرية والمخبرية وتحليلها باستخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية. النتائج: كان متوسط عمر مجموعة الدراسة 30 عامًا (المدى 11 شهرًا - 56 عامًا). كان هناك غلبة للإناث بنسبة 32.30٪ ذكور و 66.70٪ إناث. معظم المرضى (48٪) تعرضوا لأكثر من نوع واحد من النزيف بناءً على التوطين وتم تحديدهم على أنه نزيف من مواقع مختلفة ، معظمها من المفاصل والعضلات (23.90٪) ، يليها الغشاء المخاطي (14.60٪) ، والجهاز البولي التناسلي (7.70٪) ، كدمات (2.80٪) ، ونزيف معدي معوي (2.80٪). 48٪ من الأشخاص الذين يعانون من أكثر من نوع واحد من النزيف ، 105 (58.01٪) لديهم النوع الأول ، 29 (16.02٪) لديهم النوع الثاني ، و 47 (25.96٪) لديهم النوع الثالث. كان متوسط قيمة الهيموجلوبين 116 ± 25.60 جم / لتر ؛ كان الفيريتين 75.80 ± 166.80 ميكروغرام / لتر (متوسط 28.5) ؛ كان مستضد فون ويلبراند 0.40 ± 0.27 وحدة دولية / مل ، وفون ويلبراند: كان العامل المساعد ريستوسيتين 0.32 ± 0.20 وحدة دولية / ديسيلتر 49.20٪ من الأشخاص أظهروا لفترات طويلة ، وأظهر 50.80٪ وقت الثرومبوبلاستين الجزئي الطبيعي. أظهر التحليل المقارن لفصيلة الدم من النوع أو مع النوع غير أو أن فصيلة الدم مرتبطة بشكل كبير مع العامل الثامن (قيمة ب = 0.013) ، عامل فون ويلبراند: العامل المساعد للريستوسيتين (قيمة ب = 0.004 ) ، وعامل فون ويلبراند: المستضد (قيمة ب = 0.019) الاستنتاجات: كان نزيف المفاصل والعضلات أكثر العروض السريرية شيوعا في مجموعتنا. على الرغم من أن مرض فون ويلبراند من النوع الأول كان الأكثر انتشارا في مجموعتنا ، فقد لاحظنا انتشارا أعلى نسبيا من النوع الثالث والذي قد يكون بسبب الاختلافات العرقية أو تحيز الإحالة. ومستضد عامل فون ويلبراند ، مع وجود فرق أكثر وضوحا لعامل مساعد ريستوسيتين. Abstract: Objectives: This study was aimed at assessing the clinical presentations and laboratory findings among patients diagnosed with vWD at a Saudi tertiary care unit. Methods: This retrospective study included 189 patients with vWD who were followed up in our unit over 4 years. Clinical and laboratory data were collected and analyzed in SPSS. Results: The median age of the study cohort was 30 years (range 11 months–56 years). The cohort had a female preponderance, with 32.30% males and 66.70% females. Bleeding from different sites was observed, mostly from the joints and muscles (23.90%), followed by the mucus membranes (14.60%), genitourinary areas (7.70%), ecchymoses (2.80%), and gastrointestinal areas (2.80%). A total of 48% of participants presented with more than one type of bleeding. A total of 105 (58.01%) participants had type 1; 29 (16.02%) had type 2; and 47 (25.96%) had type 3 vWD. Blood tests indicated the following mean value: hemoglobin, 116 ± 25.60 gm/L; ferritin, 75.80 ± 166.80 μg/L (median 28.5); vWAg, 0.40 ± 0.27IU/ml; and vWD:RCo, 0.32 ± 0.20IU/dL. The partial thromboplastin time was prolonged in 49.20% and normal in 50.80% of participants. Platelet function analysis values were prolonged in 92.90% and normal in 7.10% of participants. Comparative analysis of the O-type and non-O blood type showed that blood type O was significantly correlated with factor VIII (p-value = 0.013), vWF:RCo (p-value = 0.004), and vWF:Ag (p-value = 0.019). Conclusion: Joint and muscle bleeds were the most common clinical presentations in our cohort. Although type 1 vWD was most prevalent in our cohort, we observed a comparatively higher prevalence of type 3, possibly because of ethnic differences or referral bias. We found a significant difference between O and non-O blood type regarding FVIII and vWF:Ag, and observed a more pronounced difference for vWD activity measuresd by vWF:RCo with blood type O being the systematic factor.